Buster catches a cold - Madokoro, Hisako, 1938-; Kuroi, Ken, 1947- (Milwaukee : Gareth Stevens Children's Books, 1991)
Buster the puppy ignores his mother's instructions and goes outside for an adventure in the rain.
Translation of: Ame no hi no Korowan.
2.3
K-3
Keywords: Dogs -- Fiction; Rain and rainfall -- Fiction; Dogs -- Fiction; Rain -- Fiction